Pengaruh Profitabilitas Dan Leverage Terhadap Nilai Perusahaan - Nadhilah, Farhana; Widjaja, Hidajat Sofyan; Kaban, Reny Fitriana (Gorontalo Accounting Journal, 2022)
This research aims analyze the significance of the effect of profitability and leverage on firm value. This research methods uses descriptive and quantitative. Analysis of the data well-used data panel regression. The results found that profitability have a significant effect on firm value. While the leverage variabel shows a significant effect to firm value. This is related to firm values. Property and real estate company is expected to consistently ameliorate the performance in order to improve profitability and leverage on firm value. Higher profitability and leverage, the higher firm value.